The relationship between blood–brain barrier dysfunction and neurocognitive impairments in first-episode psychosis: findings from a retrospective chart analysis. Issue 3 (11th May 2023) - Maurus, Isabel; Wagner, Sarah; Campana, Mattia; Roell, Lukas; Strauss, Johanna; Fernando, Piyumi; Muenz, Susanne; Eichhorn, Peter; Schmitt, Andrea; Karch, Susanne; Pogarell, Oliver; Engel, Rolf R.; et al.
Abstract : Background: Even before the onset of psychotic symptoms, individuals with schizophrenia display cognitive impairments. Simultaneously, increasing amounts of individuals exhibit dysfunction of the blood–brain barrier (BBB). However, the impact of BBB dysfunction on neurocognitive impairment in people with first-episode psychosis has not yet been investigated. Aims: To advance understanding of said relationship, we considered one of the largest first-episode psychosis cohorts with cerebrospinal fluid parameters available, and investigated whether BBB dysfunction is related to working memory, working speed and attention. Method: We conducted a retrospective chart review of 121 in-patients diagnosed with a first episode of a schizophrenia spectrum disorder. Patients underwent neurocognitive testing and a lumbar puncture within routine clinical care. To define BBB dysfunction, albumin cerebrospinal fluid/serum quotients, immunoglobulin G ratios and oligoclonal band types were evaluated, and gender-specific differences investigated. Neurocognitive functioning was assessed by the Wechsler Adult Intelligence Scale, Test of Attentional Performance and Repeatable Battery for the Assessment of Neuropsychological Status. We performed simple and multiple linear regression analyses to interpret associations of interest. Results: Of those tested, 16% showed an alteration in albumin quotients and 12% had an oligoclonal band type indicating BBB dysfunction. Notably, male patients were more likely to have an increased albumin quotient and a higher immunoglobulin G ratio than female patients. We found no significant association between BBB dysfunction and neurocognitive assessments. Conclusions: The hypothesised relationship between BBB and neurocognitive impairments was not detectable in our retrospective cohort. Further cerebrospinal fluid-based studies with a longitudinal assessment of cognitive functioning and disease trajectory are urgently needed.